The endangered Hastings River mouse (Pseudomys oralis) as a disperser of ectomycorrhizal fungi in eastern Australia. (1st November 2020) - Elliott, Todd F.; Townley, Sally; Johnstone, Charmaine; Meek, Paul; Gynther, Ian; Vernes, Karl
ABSTRACT: Rodents are the most widespread and diverse order of vertebrate mycophagists and are key to the dispersal of mycorrhizal fungi. Rodents consume and subsequently disperse fungi through their feces on every continent except Antarctica. This study examines the fungal taxa consumed by the Hastings River mouse ( Pseudomys oralis ), an endangered Australian endemic rodent from the family Muridae. We analyzed 251 fecal samples collected over a 19-year period between 1993 and 2012 at sites throughout the distribution of the animal in New South Wales and Queensland. We show that at least 16 genera of mycorrhizal fungi are eaten by this species and that it is therefore playing an important role as a vector of ectomycorrhizal truffle-like fungi in eastern Australia. Similar to the fungal diets of other mammals in eastern Australia, seasonal fungal consumption was greatest in autumn and winter. The dietary diversity of P. oralis also appeared to follow a geographic trend from south to north; samples collected at sites in the southern part of the species' range had greater diversity than those from sites in the northern part of the range, and overall, diets from southern sites yielded more fungal taxa than did northern sites. This study provides novel insights into the diet of P. oralis and highlights the importance of previously overlooked ecosystem services this species provides through its dispersal of mycorrhizal fungi.